Job Satisfaction of Engineers in Engineering Consultant Firms - Che Din, Noor Hisham (1997)
The research was carried out to determine the level of job satisfaction among engineers working in engineering consultant firms in Klang Valley, Selangor and the factors that affect the level of job satisfaction. Ten engineering consultant firms were selected for this research. The above companies were operating engineering consultancy services in the fields of Civil, Structural, Mechanical and Electrical. The size of the companies selected were varies from small to medium size. The small size company would typically have about five engineers while the medium size company would normally have about 15 to 20 engineers. The Job Descriptive Index (JDI) questionnaire has been used in this research where it consists of 72 statements from 5 facets of job satisfaction. There were 120 questionnaire sheets distributed to various engineering consultants firms. Out of this, only 51 engineers were responded to the questionnaires. From the data collected, majority (78.4%) of the respondents were moderately satisfied with their job and 3.9% of the respondents were experiencing highly satisfied with their job situation. However, only 17.7% of the respondents have expressed their dissatisfaction. Hence, it is found that majority of the respondents were moderately satisfied with their job as a whole without differentiating their demographic data.